Institutional design principles for accountability in large irrigation systems - Merrey, Douglas J. (International Irrigation Management Institute, 1996)
Argues that single irrigation systems managed by autonomous system-specific organizations accountable to their customers, perform better and are more sustainable than those managed by agencies dependent on the government, or by agencies responsible for multiple systems. Selected cases are reviewed and the plausibility of this hypothesis established. General recommendations are made for policy makers designing irrigation reform programs.